Cytokines in the Immune Microenvironment Change the Glycosylation of IgG by Regulating Intracellular Glycosyltransferases - Cao, Yedi; Song, Zhijing; Guo, Zhendong; Zhao, Xue; Gong, Yan; Zhao, Keli; Qu, Chenxue; Huang, Youyuan; Li, Yan; Gao, Ying; Zhang, Junqing; Guo, Xiaohui (Frontiers in Immunology, 2022)
Background: Changes in IgG glycosylation, as a novel pathological feature, are observed in various autoimmune diseases (AIDs). The glycosylation patterns of IgG play a critical role in regulating the biological function and stability of IgG involved in the pathophysiology of many AIDs. However, the intracellular regulatory mechanisms underlying the effects of disturbances in various cytokines on IgG glycosylation are poorly understood. Thus, we investigated the regulatory effects of elevated cytokines in AIDs on intracellular IgG glycosylation within B cells. Methods: First, we established a controlled primary culture system in vitro to differentiate human CD19+ B cells into antibody-secreting cells (ASCs). Then, the IgG concentrations in the supernatants were measured by enzyme-linked immunoassay (ELISA) under IFN-γ, TNF-α, IL-21, IL-17A, BAFF, or APRIL stimulation. Next, the glycosylation levels of IgG under different stimuli were compared via a lectin microarray. The fine carbohydrate structures of IgG were confirmed by matrix-assisted laser desorption/ionization-quadrupole ion trap-time of flight-mass spectrometry (MALDI-TOF-MS). Finally, the expression of glycosyltransferases and glycosidases in B cells under stimulation with several cytokines was detected by real-time PCR and western blotting. Results: We found that cytokines significantly promoted IgG production in vitro and led to considerably different IgG glycan patterns. Specifically, the results of lectin microarray showed the galactose level of IgG was increased by IFN-γ stimulation (p<0.05), and the sialylation of IgG was increased by IL-21 and IL-17A (p<0.05). The MALDI-TOF-MS data showed that the frequency of agalactosylation was decreased by IFN-γ with the increased frequency of mono-galactosylation and decreased frequency of digalactosylation, accompanied by upregulation of β-1,4-galactosyltransferase 1. Both frequencies of mono-sialylated and disialylated N-glycans were increased by IL-21 and IL-17A with decreased frequency of asialylation, and the expression of β-galactoside α-2,6-sialyltransferase 1 was upregulated by IL-21 and IL-17A. Conclusion: Abnormally elevated cytokines in the microenvironment regulates IgG glycan patterns by regulating intracellular glycosyltransferases in human B cells.